2015
DOI: 10.1371/journal.pone.0139445
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of Phellinus noxius and Dissemination Pattern of Brown Root Rot Disease in Taiwan

Abstract: Since the 1990s, brown root rot caused by Phellinus noxius (Corner) Cunningham has become a major tree disease in Taiwan. This fungal pathogen can infect more than 200 hardwood and softwood tree species, causing gradual to fast decline of the trees. For effective control, we must determine how the pathogen is disseminated and how the new infection center of brown root rot is established. We performed Illumina sequencing and de novo assembly of a single basidiospore isolate Daxi42 and obtained a draft genome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…However, some fungi are also one of the dominant groups of pathogens causing diseases in trees. There has been an emergence of tree disease outbreaks in different parts of the world such as ash dieback (Gross, Holdenrieder, Pautasso, Queloz, & Sieber, ), Dutch elm disease (Potter, Harwood, Knight, & Tomlinson, ), laminated root rot caused by Phellinus sulphurascens (Williams et al., ) and brown root rot caused by Phellinus noxius (Akiba et al., ; Ann, Chang, & Ko, ; Chung et al., ). Factors contributing to this phenomenon include climate change (Goberville et al., ) and human activity (Fisher et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some fungi are also one of the dominant groups of pathogens causing diseases in trees. There has been an emergence of tree disease outbreaks in different parts of the world such as ash dieback (Gross, Holdenrieder, Pautasso, Queloz, & Sieber, ), Dutch elm disease (Potter, Harwood, Knight, & Tomlinson, ), laminated root rot caused by Phellinus sulphurascens (Williams et al., ) and brown root rot caused by Phellinus noxius (Akiba et al., ; Ann, Chang, & Ko, ; Chung et al., ). Factors contributing to this phenomenon include climate change (Goberville et al., ) and human activity (Fisher et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized importance of P. noxius as an emerging pathogen, its genome, evolution and global population genetics are poorly understood. Previous reports based on simple sequence repeat (SSR) markers suggest the existence of highly diversified P. noxius populations (Akiba et al., ; Chung et al., ), but the isolates exhibited little to no host specificity (Ann et al., ; Nandris, Nicole, & Geiger, ; Sahashi, Akiba, Ishihara, Miyazaki, & Kanzaki, ). Currently, no gold standard genomes (Chain et al., ) are available for this group of wood decay fungi, which is a necessary step towards a better knowledge of their diversity, ecology and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported four Hymenochaetales genomes and revealed the nature of hyperdiversity of nuclear genomes in two lineages of P. noxium in Taiwan and Japan areas (Chung, et al 2015; Chung, et al 2017). To understand the mitochondrial genomics in Hymenochaetales, we analysed six mitogenomes in this order.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, Pyrrhoderma noxium (syn. Phellinus noxius ) (Zhou, et al 2018) has a very wide host range, spanning more than 200 broadleaved and coniferous tree species (at least 59 families), and are the causative agents responsible for brown root rot disease in parts of Asia (Akiba, et al 2015; Chung, et al 2015). A recent comparative and population genomics study of six genomes from this order and 60 P. noxium strains from Taiwan and Japan revealed that P. noxium possesses extraordinarily high diversity in its nuclear genomes (Chung, et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This fungal pathogen has become a growing concern in many countries in recent years as it would lead to swift deterioration of the health of the plant host within a year if left untreated. The pathogen is extremely infectious, and can be spread easily over short distances through root-to-root contact or contact with infected soil or wood pieces [2,3], or through air-borne basidiospores for long distance dispersal [4]. It targets the roots and water transport system of the host plants, causing root mortality and compromising tree stability.…”
Section: Introductionmentioning
confidence: 99%